Hubungan Pengetahuan Ibu dengan Penanganan Diare pada Balita di Wilayah Kerja Puskesmas Pahandut: The Correlation of Mother's Knowledge and Handling of Diarrhea in Toddlers the Work Area of Puskesmas Pahandut - Cindy Anastasiani; Fitriani Ningsih; Riska Ovany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Diarrhea is an increase in the discharge of stools with a softer or more fluid consistency than usual, and occurs at least 3 times in 24 hours. Diarrhea is the second leading cause of death in children under age five years. Therefore, the role of the mother is very important regarding good and appropriate diarrhea handling actions to reduce the incidence of diarrhea. The purpose of this study was to determine the correlation between a mother's knowledge and the handling of diarrhea in a toddler in the work area of Puskesmas Pahandut. The design of this study used descriptive analytic research with a cross-sectional approach. The sampling method used is purposive sampling. The samples taken were 44 respondents, namely mothers who had toddlers who had suffered from diarrhea in the work area of the UPT Puskesmas Pahandut. The data for this study were collected and tabulated using a questionnaire. The Chi-Square test was used to analyze the data in univariate and bivariate analysis. The results of the chi-square test have a p-value of 0.013 (0.05), which means there is a correlation between a mother's knowledge and the handling of diarrhea in toddlers in the Pahandut Health Center working area. The advice given is to increase various health promotions with media such as brochures, leaflets, and posters to mothers who have toddlers about the proper and correct handling of diarrhea.